Amphipoda (Crustacea) from Palau, Micronesia: Families Melphidippidae, Oedicerotidae, Photidae, Pleustidae, Podoceridae, Stenothoidae, Synopiidae and Talitridae - Myers, A.a. (Zootaxa, 2014)
Eleven species belonging to the families Melphidippidae, Oedicerotidae, Photidae, Pleustidae, Podoceridae, Stenothoidae, Synopiidae and Talitridae are recorded from Palau, Micronesia. Eight species are figured. One species is new to science and is described and figured. One species was previously known only from Australia, one only from Madagascar and one only from Fiji.